Test Anxiety in Pre-service English Teachers at Universidad Técnica del Norte: Ansiedad durante Pruebas en Futuros Profesores de Inglés de la Universidad Técnica del Norte - Mantilla, Marcia; Guevara-Betancourt, Sandra (Ecos de la Academia, 2023)
This research was aimed to describe test anxiety experienced by English Major students from Universidad Técnica del Norte. This study was conducted during the academic period of October 2021 – February 2022. It applied a qualitative approach whose main instrument was the Westside Test Anxiety Scale to gather the required data to identify the anxiety levels experienced during English tests. For this purpose, 250 students were the participants, the whole population of the undergraduate English program. The data was collected using an online questionnaire. The main findings evidence that anxiety before a test ranges between Moderate and High, regardless of the level, which disregard the incidence of age. Besides the existing anxiety before tests, the anxiety levels evidenced during and after them, report to be High and Extremely High for students. In conclusion, teachers must be trained in strategies to teach students how to cope appropriately with test anxiety. Therefore, pre-service English teachers were selected as the target population for this study.
Keywords: inglés; Test Anxiety; Anxiety Scale; Pre-Service English Teachers; Strategies